2006
DOI: 10.1007/s10734-004-6375-8
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ Perceptions of and Attitudes Toward (Online) Peer Assessment

Abstract: Abstract. The use of peer assessment (PA) as an alternative form of evaluation method is reported to be helpful in learning and is increasingly being adopted in higher education settings. Through collecting data from 280 university students in Taiwan, a 20-item instrument was developed to investigate university students' attitudes toward and perceptions of PA and online PA. Four subscales, Positive Attitudes, Online Attitudes, Understanding-and-Action, and Negative Attitudes, were extracted and reliabilities w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
126
1
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(144 citation statements)
references
References 33 publications
11
126
1
6
Order By: Relevance
“…Wen and Tsai (2006) found that university students' attitudes towards peer-assessment were generally positive; however, there was a lack of self-confidence in their ability to mark their classmates' work and, reciprocally, they were apprehensive about peer criticism. Karaca (2009) encountered similar results when carrying out a study into teacher trainee's opinions of peer assessment.…”
Section: Peer-assessment Reviewmentioning
confidence: 92%
“…Wen and Tsai (2006) found that university students' attitudes towards peer-assessment were generally positive; however, there was a lack of self-confidence in their ability to mark their classmates' work and, reciprocally, they were apprehensive about peer criticism. Karaca (2009) encountered similar results when carrying out a study into teacher trainee's opinions of peer assessment.…”
Section: Peer-assessment Reviewmentioning
confidence: 92%
“…Such studies using interactive feedback via technological devices were excluded, such as computer-based formative assessment (Hodgson & Pang, 2012;Hung, Lin, & Hwang, 2010;Jingzheng & Yuanbing, 2014;Wen & Tsai, 2006) and a study on mobile formative assessment by Hwang (2011).…”
Section: Journal Of Social Science Studiesmentioning
confidence: 99%
“…Some have advocated for teachers to include more peer feedback experience (Wen & Tsai, 2006), to provide more clarity about peer feedback criteria (Falchikov, 2001;Smith et al, 2002) and to provide support and training with regards to the peer feedback process (Cheng & Warren, 1997;Falchikov, 2001). Liu, Chiu, Lin & Yuan (1999) also indicated that online feedback systems may reduce the negative perspectives of peer feedback because of the anonymity of the reviewer which reduces the problematic power relations that appear between peers when assessing.…”
Section: Introductionmentioning
confidence: 99%